The Geology and Lamongan Volcanic Rocks Case Study at Ranu Pakis, Klakah, Lumajang, East Java Province, Indonesia - Dwi Fitri Yudiantoro; Ramonada Taruna Perwira; Muchamad Ocky Bayu Nugroho (UIR PRESS, 2019)
Lamongan volcano is one of the unique volcanoes in the Sunda Volcano. This volcano has side eruption centers or on the slopes of the volcano. The morphology of parasitic eruptions in this volcanoes complex includes maars and boccas. There are about 64 parasitic eruption centers consisting of 37 volcanic cones (bocca) and 27 ranu (maar). The purpose of this research is to study the characteristics of lithology and petrogenesis of this volcano complex, especially in Ranu Pakis and surrounding areas. The analytical method used is to do geological mapping and petrographic analysis. The lithology found in this research area consists of magmatic and phreatomagmatic eruption deposits. Genetically this lithology includes pyroclastic flow, pyroclastic fall (scoria fall and phreatomagmatic scoria fall/accretionary lapili), tuff (phreatic) and basaltic lava. In some pyroclastic deposits, especially in maar there are fragments of accretionary lapilli, while in bocca there are basaltic lavas. Other fragments present in pyroclastic deposits are basalt scoria blocks and bombs embedded in the groundmass of volcanic ash. The results of petrographic analysis indicate that the volcanic rocks in the study area are calc alkaline affinity consisting of pyroxene andesite, basalt and pyroxene basalt lava. The pyroxene basalt lava is composed by plagioclase, clinopyroxene and little olivine embedded in the volcanic glass. Lavas are structured scoria and textured porphyritic, intersertal, trachytic, aphyric and pilotaxitic. Trachytic texture is found in the basalt fragments of pyroxene from the pyroclastic fall deposits in Ranu Pakis and Ranu Wurung. While pyroxene andesite lavas composed by plagioclase, clinopyroxene embedded in the volcanic glass. Lavas are structured scoria and textured porphyritic, intergranular, pilotaxitic and aphyric.